Flood damage assessment model using cost-benefit analysis - Akbar, Nor Azliza (2006)
Flood is a problem caused by precipitation and runoff particularly during periods of excessively high rainfall. Nowadays in Malaysia, flood becomes a serious problem to the extent of imposing impact to the environment. This problem may cause damages to properties, loss of life, loss of utility services, loss of trading and others. However, with sophisticated technologies, some flood mitigation measures have been designed by engineers. Every year, the government allocates huge amount of money for flood control projects. A study on flood damage assessment is necessary to identify, predict and evaluate the benefits of flood control projects. Thus, a model on flood damage assessment was developed by using Visual Basic 6.0 (VB6.0) language and the data which is used in this calculation is hypothetical data. The analysis was carried out in real time such that user may put the inventory data taken from various places and the result will be displayed in a graphical form. Besides, this study is important to ensure that floods are controlled by constructing flood control measures and to minimise damages to the environment. Indeed, an economic analysis plays an important role in deciding between various alternative projects available. From the analysis, more combinations of flood control schemes used may reduce more damages but it also increases the cost of flood control projects. The best approach to establish the most economical flood control system was selected based on which system gives the largest benefit-cost ratio or the maximum net benefit. The model is able to assist engineers to make the best decision in the planning of flood control projects before the design can be implemented.